Public beliefs about trauma and its consequences: Profiles and correlates of stigma - Clapp, Joshua D.; Sowers, Alexandria F.; Freng, Scott A.; Elmi, Layla M.; Kaya, Robert A.; Bachtel, Alicia R. (Frontiers in Psychology, 2023)
Public stereotypes about trauma exposure and its likely consequences have the potential to influence levels of support extended to survivors in the larger community. The current project sought to examine unique profiles of stereotype endorsement both within and across participants sampled from distinct populations. Trauma-related stereotypes involving symptom course, dangerousness, employability, social functioning, predictability, character, and treatment need were examined in undergraduate (N1 = 404; N2 = 502) and MTurk (N3 = 364) samples. Sympathizing [low overall endorsement], Fearful [high overall endorsement], Pejorative [high endorsement + moralizing beliefs], Safety-Focused [intermediate endorsement + dangerousness], and Performance-Focused [intermediate endorsement + employability] groups were replicated in latent profile models across all samples. Stereotype profiles demonstrated hypothesized associations with general perspectives of mental illness although support for consistent relations with respondent characteristics (e.g., sex; personal exposure to trauma; reported exposure in friends/family) was limited. Data suggest that trauma stereotypes are endorsed at high frequencies in the general community and conform to systematic patterns of prejudice that may be overlooked in more global assessments of stigma.